Episodic future thinking together with observational learning benefits prospective memory in high‐functioning Korsakoff's syndrome patients. - Lloyd, Beth; Oudman, Erik; Altgassen, Mareike; Walvoort, Serge J. W.; Kessels, Roy P. C.; Postma, Albert (British Journal of Clinical Psychology, 2020)
Objective: Patients with Korsakoff's syndrome (KS) have difficulty carrying out tasks which rely on prospective memory (PM). Since remembering to carry out an action in the future is crucial for living independently, it is of primary interest to develop strategies that improve PM performance in KS patients. Design: The study employed a computer categorization task as an ongoing activity into which a PM task was embedded. We included episodic future thinking (EFT) and observational learning (Experiment 2) to boost PM. Methods: Experiment 1 evaluated the efficacy of EFT following written PM task instructions in ten KS patients. Due to floor‐level PM performance in Experiment 1, Experiment 2 included an instructional video demonstrating the PM intention. In Experiment 2, twenty‐six KS patients performed both conditions (EFT and no‐EFT) at least 1 week apart, while twelve controls with alcohol use disorder without KS performed the no‐EFT condition. In Experiment 2, the PM instructions were also shown through video (observational learning component). Mild cognitive impairment was assessed in a short test battery. Results: Experiment 1 showed overall floor performance in both conditions. Experiment 2 showed that KS patients performed PM tasks less accurately than the control group in the no‐EFT condition. In Experiment 2, where the observational learning component was included, EFT improved PM performance in KS patients. This effect was driven by a sub‐group of high‐functioning KS patients. Conclusions: This study showed the value of an observational learning component together with EFT in improving PM performance, in relatively high‐functioning KS patients. Practitioner points: KS patients performed the PM task less accurately than non‐KS controls with alcohol use disorder, confirming PM impairment in this patient population.Controls with alcohol use disorder performed the PM task at ceiling level.Showing an instructional video demonstrating the PM intention improved PM performance and later recall of PM task instructions in KS patients.Episodic future thinking strategy improved PM performance in KS patients with relatively intact cognitive functioning.